Mulheres negras e baile funk: sexualidade, violência e lazer - Iara Felix Viana (2013)
This study has the purpose of analyzing the process of social construction of femininity in a popular district favelizado called set Morro Alto, Vespasian-MG, as well as its links with violence and power in moments of leisure in funk parties. Thus, knowing the trajectory, the everyday life of young girls / women, glancing about the processes of construction of the senses about their activities, with respect to being a woman and becoming a woman, its historicity and complexity, represented an effort relevant to the production of this paper. This research was supported by a qualitative approach, in which semi-structured interviews were conducted, the type field observation and participant discussion groups with young girls / women, and members of groups funqueiras / Trams. Worked with the following theoretical categories organizers of study: leisure, gender, femininity, youth, violence, and during the study, emerged as explanatory categories researched field: attend the dance and funk, and the training of your Trams belonging, the meanings to recognize themselves as periguete, feminine empowerment in public and in private popular districts. It was found that the life trajectories of girls / women are marked by distinct actions for coping in male territories that challenge gender relations, stemming initially transgressions both at home and on the street. The territory represented a funk spaces favorable to criticism of supposedly prescribed a reality in which they become subjects of their actions producing a singular feminine ethos.